Impact of social and occupational factors over job control - Moreno-Pimentel, Antonio G; Meneses Monroy, Alfonso; Martín-Casas, Patricia; Zaragoza-García, Ignacio; Girón-Daviña, Pedro (La Medicina del Lavoro, 2019)
Background: Psychosocial risk factors, among which job control has proved to be a key dimension, can have a negative impact on the health of workers. Various research projects have found a relationship between low levels of free time at work and stress and job satisfaction indicators. Objectives: to assess to what extent certain social and employment variables influence “job control”. Methods: A descriptive study was carried out on a sample of workers to analyse the influence of certain socio-demographic and work-related variables on job control, by means of an assessment survey on psychosocial risk and the general state of workers’ health. The tools used in this study were the COPSOQ-ISTAS 21 version 1.5 psychosocial risk assessment questionnaire and a specific survey on the perceived state of health. Results: Three hundred fourteen workers were asked to participate in the study. One hundred and ninety workers completed the questionnaire and were finally included. For the “job control” variable, 47.4% of workers described their situation as good. The results show that workers with a higher educational level (+78%), who have seniority in the job, have a good understanding of their situation at work (+15%), and are employed as white collars (34%), are more likely to show high job control and, therefore, could be less at risk from psychosocial factors. Conclusions: There are two parameters influencing “job control”: social factors concerning educational level, and work situation factors, including seniority and being a white collar worker.